PENDIDIKAN ISLAM DI ERA DISRUPSI PRESPEKTIF IBNU KHALDUN - Eka Wahyu Hidayati (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
Islamic education is an effort in planning to prepare people to recognize, understand, appreciate, and believe in the teachings of the Islamic religion accompanied by demands to respect other religions in inter-religious relations to create national unity and integrity. This article aims to provide readers with new knowledge about the concept of Islamic education in the era of disruption based on the perspective of Ibn Khaldun's Islamic education. This study uses a literature study approach by using descriptive analysis. The results of this study indicate that Islamic education is used as a filter for students to be able to balance the development of technology and Islamic law as a process where students are able to appreciate, absorb and even capture events throughout the ages.